Mechanistic Physiologically Based Pharmacokinetic Modeling of Dry Powder and Nebulized Formulations of Orally Inhaled TMEM16A Potentiator GDC‐6988 - Rui Zhu; Ian Sorrell; Fang Ma; Miaoran Ning; Yoen‐Ju Son; Gaohong She; Tom De Bruyn; Joshua Galanter; Nastya Kassir; Ryan Owen; Masoud Jamei; Iain Gardner; et al. (CPT: Pharmacometrics & Systems Pharmacology)
ABSTRACT The orally inhaled route of administration for respiratory indications can maximize drug exposure to the site of action (lung) to increase efficacy while minimizing systemic exposure to achieve an improved safety profile. However, due to the difficulty of taking samples from different regions of the human lung, often only systemic pharmacokinetic (PK) samples are taken and assumed to be reflective of the lung PK of the compound, which may not always be the case. In this study, a mechanistic lung physiologically based pharmacokinetic (PBPK) model was built using a middle‐out approach (i.e., combining elements of bottom‐up prediction and using clinical data to inform some model parameters) to predict plasma and lung PK of an orally inhaled TMEM16A potentiator GDC‐6988 in humans. The lung PBPK model accounted for lung deposition, lung and oral absorption, systemic clearance, and tissue distribution. The model was refined using data from a Phase 1b study with dry powder (DP) formulation and was also verified using data from a Phase 1 study with a nebulized (Neb) formulation. The refined model adequately captures the observed GDC‐6988 plasma PK profiles in both the DP and Neb studies and allows prediction of the regional lung fluid and tissue concentrations. The sensitivity analyses showed that the systemic Cmax depended on the ratio of airway to alveolar deposition, but this did not impact the AUC. This novel mechanistic lung PBPK modeling framework could be applied to predict plasma and regional lung exposure and inform the early clinical development of inhaled molecules (e.g., dose selection).